2019
DOI: 10.1021/acs.cgd.9b00028
|View full text |Cite
|
Sign up to set email alerts
|

From Th-Rhabdophane to Monazite-Cheralite Solid Solutions: Thermal Behavior of Nd1–2xThxCaxPO4·nH2O (x = 0–0.15)

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
3
12
0
Order By: Relevance
“…Finally, the last shrinkage step evidenced on the dilatometric curve was observed typically above 1000°C and was correlated to the sintering of the J o u r n a l P r e -p r o o f samples. This result fits well with our previous study [15] and with the data reported by Bregiroux et al…”
Section: Dilatometric Studysupporting
confidence: 94%
See 1 more Smart Citation
“…Finally, the last shrinkage step evidenced on the dilatometric curve was observed typically above 1000°C and was correlated to the sintering of the J o u r n a l P r e -p r o o f samples. This result fits well with our previous study [15] and with the data reported by Bregiroux et al…”
Section: Dilatometric Studysupporting
confidence: 94%
“…Later, the as-synthesized rhabdophanes were successfully converted into single-phase monazite-cheralite solid solutions, Ln 1-2x Th x Ca x PO 4 . Both dehydration and conversion steps of the rhabdophane precursors were monitored and investigated [15], showing that pure monazite-cheralite could be obtained by simply heating Thrhabdophane synthesized in hydrothermal conditions at T = 1100°C. Nevertheless, the possibility to obtain high-density monazite-cheralite ceramics directly from the associated rhabdophane precursor remained unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24] This conclusion can be generalized to other natural metastable minerals having hydrothermal origins, such as the dichotomy pairs of monazite-rhabdophane or xenotimechurchite. 3,9,109,110 For this reason, in order to compare high temperature structural data of stetindite and coffinite with other metal orthosilicates, such as zircon, hafnon, and thorite reported in studies of Mursic et al 111 , Ding et al 112 and Knyazev et al 89 (Table 2), 89,[111][112][113][114][115] we used the XRD data obtained during cooling where samples were fully dehydrated or dehydroxylated. In addition, we normalized all the data by taking the relative change in unit cell parameters (a/a0 and c/c0) as a function of temperature (Figure 14).…”
Section: Thermal Response Of Metal Orthosilicatesmentioning
confidence: 99%
“…10 Fortuitously, the priority formation of rhabdophane precipitations on monazite surface prevents the further degradation of monazite in leachates. [12][13][14][15][16] Recent dissolution experiments reveal the chemical stability of Ce 1−x Gd x PO 4 monazite will be weaken with increasing the concentration of Gd, and Gd is more likely to be dissolved compared to Ce. 17 Similar phenomenon has been observed in Ce 0.5 Eu 0.5 PO 4 monazite, associated with the leaching rate of Eu is half lower than that of Ce, 18 implying lanthanides have different stability in monazite.…”
Section: Methodsmentioning
confidence: 99%
“…Extremely low leaching concentration of actinides when synthetic monazite waste forms dissolving in deionized water shows that doped actinides can closely bound with oxygen in monazite matrix 10 . Fortuitously, the priority formation of rhabdophane precipitations on monazite surface prevents the further degradation of monazite in leachates 12–16 . Recent dissolution experiments reveal the chemical stability of Ce 1− x Gd x PO 4 monazite will be weaken with increasing the concentration of Gd, and Gd is more likely to be dissolved compared to Ce 17 .…”
Section: Introductionmentioning
confidence: 99%